Implementing a self-management mobile app for spinal cord injury during inpatient rehabilitation and following community discharge: A feasibility study. (2nd September 2020) - MacGillivray, Megan K.; Sadeghi, Mahsa; Mills, Patricia B.; Adams, Jared; Sawatzky, Bonita J.; Mortenson, W. Ben
Abstract : Objective: To determine the feasibility of implementing and evaluating a self-management mobile app for spinal cord injury (SCI) during inpatient rehabilitation and following community discharge. Design: Pilot feasibility study. Setting: Rehabilitation hospital and community. Participants: Inpatients from rehabilitation hospital following admission for their first SCI. Intervention: A mobile app was developed to facilitate self-management following SCI. The app consisted of 18 tools focusing on goal setting, tracking various health aspects, and identifying confidence regarding components of self-management. In-person training and follow-up sessions were conducted during inpatient rehabilitation and follow-up calls were provided after participants were discharged into the community. Main outcome measures: Participants completed outcome measures at baseline, community discharge, and 3-months post discharge. This study focused on feasibility indicators including recruitment, retention, respondent characteristics, adherence, and app usage. Additionally, participants' self-management confidence relating to SCI (e.g. medication, skin, bladder, pain) was evaluated over time. Results: Twenty participants (median age 39, IQR: 31 years, 85% male) enrolled in the study. Participants' Spinal Cord Injury Independence Measure (SCIM-III) median score was 23 and IQR was 33 (range: 7–84), which did not correlate with app usage. Retention from admission to discharge was 85% and 70% from discharge to 3-months post discharge. Individuals in the study who used the app entered data an average of 1.7x/day in rehabilitation ( n = 17), and 0.5x/day in the community ( n = 7). Participants' bowel self-management confidence improved between admission and discharge ( P < 0.01). Conclusions: Feasibility indicators support a larger clinical trial during inpatient rehabilitation; however, there were challenges with retention and adherence following community discharge.